A Rare Big Chinese Family With Thrombocytopenia 2: A Case Report and Literature Review - Tan, Chengning; Dai, Limeng; Chen, Zhengqiong; Yang, Wuchen; Wang, Yali; Zeng, Cheng; Xiang, Zheng; Wang, Xiaojie; Zhang, Xiaomei; Ran, Qian; Guo, Hong; Li, Zhongjun; et al. (Frontiers in Genetics, 2020)
Thrombocytopenia 2 (THC2) is one of the most prevalent forms of inherited thrombocytopenia. It is caused by a heterogeneous group of ANKRD26 gene mutation and shows a heterogeneous clinical and laboratory characteristics. We present a big Chinese family with 10 THC2 patients carrying c.-128G>T heterozygous substitution in the 5-untranslated region of the ANKRD26 gene. Although the platelets are fewer than 50 × 109/L in 8 THC2 family members, only the proband and her son show a higher WHO bleeding score. The proband and her son are also beta-thalassemia carriers with heterozygous c.52A>T mutation of HBB, which might not be associated with the increased bleeding tendency since 3 other family members with low bleeding tendency also carried both ANKRD26 c.-128G>T and HBB c.52A>T mutations. However, the proband and her son also show hypofibrinogenaemia, which is likely the cause of their more severe clinical manifestation. HID1 c.442G>T mutation was detected not only in these two hypofibrinogenaemia family members but also in the other 8 family members with normal blood fibrinogen levels. Our study suggests that the co-occurrence of other inherited genetic conditions associated with blood coagulation might contribute to the heterogeneity of clinical and laboratory characteristics in THC2 patients. Considering the hematologic and myeloid malignancy predisposition of THC2 patients and a large population of immune thrombocytopenia in China, we urge more attention to be paid to the diagnosis of THC2 patients to avoid misdiagnosis and mistreatment.